Comportamiento de las estructuras de madera construidas en la Estancia Jesuítica de Santa Catalina en el siglo XVII - Gómez, J. L.; Fernández Saiz, M. del C.; Papalardo, L. (Revista ALCONPAT, 2014)
This paper presents a study of wooden structural typologies used by the Jesuits in the "Estancia de Santa Catalina", Córdoba Province. The wood used in beams and columns was characterized at microscopic and macroscopic levels. Tests were carried out to determine the physical and mechanical characteristics; the soundness of the structure was evaluated by following the Brazilian standard BR7190 for the verification of the strength and deformability. We studied the reticulated structures, showing the pathological manifestations in the structural elements and making a diagnosis that allowed the estimation of their degree of safety. The study highlights the outstanding durability of the wood older than 360 years; it also recommends proceedings for the recovery of damaged parts and maintenance of these constructions that have been declared common heritage of mankind. Keywords: Wooden Structures, patrimony, heritage durability